2012
DOI: 10.1002/ange.201108043
|View full text |Cite
|
Sign up to set email alerts
|

Strong Metallophilic Interactions in the Palladium Arylation by Gold Aryls

Abstract: and the Junta de Castilla y León (VA281A11-2 and VA373A11-2) for financial support; CESGA for generous allocation of computational resources; and Dr. JosØ M. Aurrecoechea (Universidad del País Vasco) for discussions.Supporting information for this article is available on the WWW under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The overall thermodynamic data for the transmetalation step compared to the cis ‐complex [PdXPhL 2 ] ( cis ‐ 1 a , c ) is Δ G trans =+1.4 kcal mol −1 (X=Cl) and Δ G trans =−0.9 kcal mol −1 (X=I), respectively, is in accord with the thermodynamic results for the transmetalation reaction employing the chelate ligand on Pd (Table 2). Interestingly, the transmetalation thermodynamics are highly endergonic Δ G trans =+13.5 kcal mol −1 (X=Cl); Δ G trans =+10.2 kcal mol −1 (X=I) if compared with the trans ‐[PdXPhL 2 ] complex ( trans ‐ 1 a , c ), which is in good agreement with the experimental and theoretical results by Espinet et al 16a. studying the favored (exergonic) transmetalation from Pd to Au starting with [PdR 2 L 2 ].…”
Section: Computational Resultssupporting
confidence: 90%
“…The overall thermodynamic data for the transmetalation step compared to the cis ‐complex [PdXPhL 2 ] ( cis ‐ 1 a , c ) is Δ G trans =+1.4 kcal mol −1 (X=Cl) and Δ G trans =−0.9 kcal mol −1 (X=I), respectively, is in accord with the thermodynamic results for the transmetalation reaction employing the chelate ligand on Pd (Table 2). Interestingly, the transmetalation thermodynamics are highly endergonic Δ G trans =+13.5 kcal mol −1 (X=Cl); Δ G trans =+10.2 kcal mol −1 (X=I) if compared with the trans ‐[PdXPhL 2 ] complex ( trans ‐ 1 a , c ), which is in good agreement with the experimental and theoretical results by Espinet et al 16a. studying the favored (exergonic) transmetalation from Pd to Au starting with [PdR 2 L 2 ].…”
Section: Computational Resultssupporting
confidence: 90%
“…The aim of bimetallic catalysis is to take advantage of the specific behavior of each catalyst in new one‐pot synthetic routes. For the Au/Pd couple it is known that the Au/Pd transmetalation, a step which is hoped to connect the palladium and the gold catalytic cycles, is kinetically feasible,2, 3 even for fairly bulky groups 4. However, so far only a few Au/Pd bimetallic catalyzed processes have been reported, including the Sonogashira‐like cross‐coupling,5 the carbometallation of alkynes,6 and processes combining cyclization with cross‐coupling steps 7.…”
Section: Methodsmentioning
confidence: 99%
“…The calculations were performed for the formation of (2‐methyl‐1‐(4‐(trifluoromethyl)phenyl)naphthalene (Table 2, entry 7) with the real molecules, except for the Sn( n Bu) 3 group, which was simplified to SnMe 3 . The transmetalation mechanisms from tin to palladium and from gold to palladium have been studied before for sterically nondemanding groups 3. 23 The transmetalation mechanism from tin to gold has not been studied so far, and is depicted in Scheme .…”
Section: Methodsmentioning
confidence: 99%
“…As evidenced by the Lewis-Mayo plot, it is observed that the organogold monomer is built in more rapidly at the beginning of the polymerization, which can be explained by the favourable gold-palladium interactions. [31][32][33][34][35][36][37] As a consequence, a considerable amount of AuPtBu3Br is released into the reaction mixture at quite low conversions, which could possibly transmetallate with the stannylated butylthiophene monomer. 31 To investigate whether this reaction is actually occurring, AuPtBu3Br was synthesized by reacting AuPtBu3Cl with KBr in acetone.…”
Section: Copolymerizationmentioning
confidence: 99%